The Value of Having an Expert Sports Performance and Medicine Staff in the National Football League - David LaPlaca; Jeremy Elliott (International Universities Strength and Conditioning Association, 2021)
An expert strength and conditioning coach can be an important component of a sports performance and medicine staff that will train their athletes to help them become more resilient to injury. Previous research in a variety of sports has shown that teams with players that have fewer games missed due to injury have achieved greater success. The purpose of this study was to determine if a relationship exists between games missed due to injury by offensive and defensive starters on National Football League (NFL) rosters and a NFL team's ability to win during the 2010-19 NFL seasons. A Spearman rank-order correlation analysis set at (p ≤ 0.01) level of significance indicated that fewer games missed by starters in the NFL is correlated with multiple variables associated with winning such as games won per season and playoff appearances. These results were obtained after analyzing all 32 NFL teams from the 2010-19 seasons. Descriptive statistics were also used to further analyze the data set and found that teams ranked in the top-five in terms of fewest injuries outperformed the remainder of the teams in the NFL according to multiple variables associated with winning. The data in this study supports that NFL organizations should look to reduce the games missed due to injury of their athletes, which may be accomplished through hiring expert sports performance and medicine staff members, such as a strength and conditioning. hire an expert strength and conditioning coach capable of reducing the risk of athletes getting injured in order to increase their team's chances of winning.